INSURGENCY AND BASIS EDUCATION IN NIGERIA EDUCATION - NISHANT KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
Every country on earth works hard to provide its citizens with a high standard of living and education, to provide a robust and diversified economic basis, to foster internal cohesion, and to preserve political stability. It is impossible to achieve this goal unless there is peaceful cohabitation and an environment that supports and fosters progress. The attacks by Boko Haram on educational institutions have led to the destruction of schools and the infliction of hardship on both the pupils and the professors who work at these kinds of establishments. Since 2009, Boko Haram has targeted schools, students, and instructors in the states of Borno, Yobe, Adamawa, and Kano with assaults that have gotten more savage. Because of the fighting, there has been a significant reduction in the number of children who have attended school or who have not attended school at all. The fact that Nigeria’s security forces have used schools as military outposts are one of the factors that have contributed to the situation. Between the years 2009 and 2015, Boko Haram was responsible for the destruction of more than 910 educational facilities and the closure of at least 1,500 schools, according to reports by Human Rights Watch (HRW). "2,295 educators were slaughtered in attacks by terrorists in the North-east," Nigeria’s Minister of Education Adamu Adamu is quoted as saying in a statement that was released by the government. Nigeria (Premium Times, June 6, 2018), where an additional 19,000 people were compelled to flee their homes for fear of being murdered, as a result of the violence. The organization is responsible for the abduction of around 2,000 people, including a considerable number of students as well as a number of women and girls.